Educação cooperativista e mídias sociais: uma análise das estratégias do sicoob SC/RS para captação e fidelização de cooperados. - Assunção, Raynnara da Silva (Universidade Federal do Tocantins, 2023)
This article analyzes the Cooperative Education and digital media of a Credit Cooperative. The research consists of the analysis of Sicoob SC / RS strategies for capturing and loyalty of the members through the social network Facebook. The article begins with a literary review on the emergence of cooperativism and its evolution in Brazil, following the importance of Cooperative Education and a chapter conceptualizing the Digital Media as a way of disseminating cooperative practices. The research was characterized as qualitative and exploratory. For data collection, bibliographical and documentary research was chosen. Among the main results, it was noticed that the main tool to attract members and loyal partners was an easy-to-use application. Another important point was the concern to disseminate some of the cooperative principles in their publications.